(untitled) (Revista Electrónica Calidad en la Educación Superior, 2023)
This article presents one of the specific objectives of the research on Pedagogical Mediation in Virtual Learning Environments in the Natural Resources Management Program at the UNED in Costa Rica. Using a qualitative approach and an action research design, the first stage of approach and diagnosis was carried out with the purpose of identifying the elements that compose pedagogical mediation in virtual environments in the teaching and learning process in the distance education model of UNED. The sources of information were chosen at the convenience of the researcher and voluntary participation of representatives from the areas of support in the teaching and learning process of the program. A virtual group session was conducted with a thematic study guide. Open and axial coding was performed using Atlas ti8® software, obtaining a definition of pedagogical mediation in virtual environments as well as the elements classified into cinco categories of welcome, design, communication, content, and evaluation, and 12 subcategories such as general information, accessibility, visual architecture, digital written materials, audiovisual materials, interaction, sections, learning strategies, feedback, types of learning, types of evaluation, and grading instruments.